Studying Function and Behavior in the Fossil Record - Benton, Michael J. (PLOS Biology, 2010)
It is easy to dismiss reconstructed organisms and behaviors from the past as “mere speculation”, but empirical evidence, comparison with modern analogs, and biomechanical modeling can provide remarkable insights.